PENAKSIR RATIO-CUM-PRODUCT YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS - Liza Yarmanita; Arisman Adnan; Firdaus ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article reviews three ratio-cum-product estimators for the population mean insimple random sampling. The coefficient of variation and the coefficient of kurtosis ofauxiliary variables are used. This article is the review of Tailor’s et. al. Article[Communications of the Korean Statistical Society 18(2):155-164]. The estimatorsdiscussed are ratio-cum-product estimator, type 1 and type 2 ratio-cum-productestimators using coefficient of variation and coefficient of kurtosis. These estimators arebiased. Then, the mean square errors (MSE) of each estimator are compared to showwhich one is the most efficient estimator. The type 2 ratio-cum-product estimator usingthe information on coefficient of variation and coefficient of kurtosis is the mostefficient estimator among the other two estimators.